Clinical Significance of Hotspot Mutation Analysis of Urinary Cell-Free DNA in Urothelial Bladder Cancer - Hayashi, Yujiro; Fujita, Kazutoshi; Matsuzaki, Kyosuke; Eich, Marie-Lisa; Tomiyama, Eisuke; Matsushita, Makoto; Koh, Yoko; Nakano, Kosuke; Wang, Cong; Ishizuya, Yu; Kato, Taigo; Hatano, Koji; et al. (Frontiers in Oncology, 2020)
Recent studies showed the clinical utility of next-generation sequencing of urinary cell-free DNA (cfDNA) from patients with urothelial bladder cancer (UBC). In this study, we aimed to develop urinary cfDNA analysis by droplet digital PCR (ddPCR) as a high-throughput and rapid assay for UBC detection and prognosis. We analyzed urinary cfDNA of 202 samples from 2 cohorts. Test cohort was designed for investigating clinical utility of urinary cfDNA, and was composed of 74 samples from patients with UBC, and 52 samples of benign hematuria patients. Validation cohort was designed for validation and assessment of clinical utility comparing urinary cfDNA with UroVysion (Abbott, Illinois, USA), and was composed of 40 samples from patients with UBC, and 36 prospectively collected samples from patients under surveillance after surgery for urothelial carcinoma. We performed ddPCR analysis of hotspot gene mutations (TERT promoter and FGFR3). In the test cohort, the sensitivity of urinary cfDNA diagnosis was 68.9% (51/74) and the specificity was 100% in patients with UBC. The sensitivity increased to 85.9% when used in conjunction with urine cytology. In addition, patients with high TERT C228T allele frequency (≥10%) had significantly worse prognosis in bladder tumor recurrence than patients with low TERT C228T allele frequency or negative TERT C228T (p=0.0338). In the validation cohort, the sensitivity of urinary cfDNA was 57.5% (23/40) and the specificity was 100% in UBC patients. The sensitivity of the combination of urine cytology with our hotspot analysis (77.5%) was higher than that of urine cytology with UroVysion (68.9%). In the post-surgical surveillance group, patients positive for the TERT C228T mutation had significantly worse prognosis for bladder tumor recurrence than mutation negative patients (p<0.001). In conclusion, ddPCR analysis of urinary cfDNA is a simple and promising assay for the clinical setting, surpassing UroVysion for detection and prognosis determination in UBC.